Efeitos da inserç\~ao de produtos da agricultura familiar na alimentaç\~ao escolar sobre o desempenho de alunos da rede pública no Brasil - Sandro Pereira Silva; Juliane da Silva Ciríaco; Eduardo Luiz Zen (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– This study sought to analyze the impact of the National School Food Program (Programa Nacional de Alimentaç\~ao Escolar - PNAE), more precisely the insertion of family farming in the supply of food products to schools (Law No. 11,947/2009), on the grades of elementary school students, using data from the Basic Education Assessment System (Sistema de Avaliaç\~ao da Educaç\~ao Básica - Saeb) in the subjects of Portuguese and Mathematics in the years 2013 and 2019. The results indicated a significant and positive correlation between purchases from family farming and the performance of elementary school students in the Saeb tests, as demonstrated by three empirical analysis models. Such findings highlight the multidimensional character of the PNAE as a national public policy, given that its effectiveness goes beyond nutritional assistance to students.
Keywords: H52; H75; I24; 330; school feeding; public purchasing; family farming; school performance; basic education